The Impact of State Legislation and Model Policies on Bullying in Schools. (2nd March 2018) - Terry, Amanda
ABSTRACT: BACKGROUND: The purpose of this study was to determine the impact of the coverage of state legislation and the expansiveness ratings of state model policies on the state‐level prevalence of bullying in schools. METHODS: The state‐level prevalence of bullying in schools was based on cross‐sectional data from the 2013 High School Youth Risk Behavior Survey. Multiple regression was conducted to determine whether the coverage of state legislation and the expansiveness rating of a state model policy affected the state‐level prevalence of bullying in schools. RESULTS: The purpose and definition category of components in state legislation and the expansiveness rating of a state model policy were statistically significant predictors of the state‐level prevalence of bullying in schools. The other 3 categories of components in state legislation—District Policy Development and Review, District Policy Components, and Additional Components—were not statistically significant predictors in the model. CONCLUSIONS: Extensive coverage in the purpose and definition category of components in state legislation and a high expansiveness rating of a state model policy may be important in efforts to reduce bullying in schools. Improving these areas may reduce the state‐level prevalence of bullying in schools.